Main Tasks and Implementation of Art Pedagogy (Eurasian Journal of Media and Communications, 2023)
Art pedagogy today is one of the most actively developing areas of scientific knowledge. Despite the fact that the concept of “art pedagogy” as a special direction in modern pedagogical science, today in Russia has not yet received a sufficiently complete and accurate definition, creatively thinking teachers are increasingly beginning to use various techniques, methods and technologies in their practice art pedagogy. We can confidently say that every year this direction is increasingly asserting itself in the modern educational and cultural space of Uzbekistan